Single stage repair of anorectal malformation with rectovestibular fistula in adult. (December 2021) - Bhavsar, Ruchir; Ray, Samrat; Verma, Muni; Agarwal, Satish K.; Nundy, Samiran
Abstract: Anorectal malformations are a wide spectrum of disorders, affecting both genders and rare adult presentation as with increased knowledge and advancements, the majority of cases are diagnosed and rectified at birth. This case is a classic example of delayed presentation caused by illiteracy and a lack of adequate health care in rural locations and highlights the uniqueness of this disease, presentation in adult age group and its management and effect on patient psychology and mental health. Because all low anorectal abnormalities can be treated in a single stage, neonatal assessment at birth and early referral to advanced health care centres are critical, with anterior or posterior sagittal anorectoplasty performed by the age of six months. Concerning the anomaly, parent education is an important aspect of patient care. Highlights: Due to a lack of advanced health care and illiteracy in rural regions, this case is a classic example of delayed presentation. All anorectal abnormalities can be addressed by anterior or posterior sagittal anorectoplasty, ideally by the age of six months. Correction of deformity beyond adolescence has a negative impact on psychosocial and emotional functioning in these people. Parental education regarding the abnormality is an important element of patient care.